1992
DOI: 10.1099/00221287-138-10-2113
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and phenotypic characterization of methanol oxidation mutants of the restricted facultative methylotroph Methylophaga marina

Abstract: Methanol oxidation in Mefhyfophuga marina appears to be organized in a way similar to that in other Gramnegative methylotrophs, involving a quinoprotein methanol dehydrogenase (MDH; EC 1.1.99.8) and two soluble cytochromes. The MDH is composed of two different subunits, most probably arranged in an a2P2 structure. The two cytochromes are of the e-type and differ in size (molecular mass 19.5 and 12.5 kDa) and isoelectric point (PI 4.6 and 9.2). The one with the lowest isoelectric point, commonly designated as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…MDH is a 2,7,9-tricarboxy-lH-pyrrolo-[2,3-f] quinoline-4,5-dione (PQQ) dependent enzyme (Duine et al 1986) and three different redox forms, having distinct absorption spectra, have been identified so far (Duine and Frank 1980; Correspondence to: Claude Balny, Institut National de la Sant~ et de la Recherche M6dicale, U128, CNRS, BP 5051, F-34033 Montpellier C6dex 1, France; Tel. Several reports indicate that MDH is composed of two different subunits with M = 60-70 kDa and M= 6-10 kDa, respectively, arranged in an ezB2 structure (Nunn et al 1989;van Spanning et al 1991;Anderson and Lidstrom 1988) and this has also been shown to be the case for the MDH from Methylophaga marina 42 used in the present study (Janvier et al 1992). Several reports indicate that MDH is composed of two different subunits with M = 60-70 kDa and M= 6-10 kDa, respectively, arranged in an ezB2 structure (Nunn et al 1989;van Spanning et al 1991;Anderson and Lidstrom 1988) and this has also been shown to be the case for the MDH from Methylophaga marina 42 used in the present study (Janvier et al 1992).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…MDH is a 2,7,9-tricarboxy-lH-pyrrolo-[2,3-f] quinoline-4,5-dione (PQQ) dependent enzyme (Duine et al 1986) and three different redox forms, having distinct absorption spectra, have been identified so far (Duine and Frank 1980; Correspondence to: Claude Balny, Institut National de la Sant~ et de la Recherche M6dicale, U128, CNRS, BP 5051, F-34033 Montpellier C6dex 1, France; Tel. Several reports indicate that MDH is composed of two different subunits with M = 60-70 kDa and M= 6-10 kDa, respectively, arranged in an ezB2 structure (Nunn et al 1989;van Spanning et al 1991;Anderson and Lidstrom 1988) and this has also been shown to be the case for the MDH from Methylophaga marina 42 used in the present study (Janvier et al 1992). Several reports indicate that MDH is composed of two different subunits with M = 60-70 kDa and M= 6-10 kDa, respectively, arranged in an ezB2 structure (Nunn et al 1989;van Spanning et al 1991;Anderson and Lidstrom 1988) and this has also been shown to be the case for the MDH from Methylophaga marina 42 used in the present study (Janvier et al 1992).…”
Section: Introductionsupporting
confidence: 69%
“…MDH and cytochrome c L were prepared from frozen cell paste of Methylophaga marina 42 as previously described (Janvier et al 1992). Wurster's blue was prepared by oxidation of N,N,N',N' tetramethyl-p-phenylene diamine (Michaelis and Gramick 1943).…”
Section: Enzymes Reagents and Solutionsmentioning
confidence: 99%
“…Ribonuclease-A (EC 3.1.27.5) was from Sigma, St. Louis, methanol dehydrogenase (MEOH-DH) was isolated from Methylophaga marina as described previously (Janvier et al 1992) and adrenodoxin was isolated from bovine adrenal cortex (Suhara et al 1972;Lange et al 1988). The final enzyme concentrations were: adrenodoxin, 50 gM, ribonuclease-A, 73 gM, and methanol dehydrogenase, Figure 1 illustrates the power of fourth derivative spectroscopy: the zero-order UV spectrum only shows a very small undulation around 265 nm, while the fourth derivative spectrum reveals the characteristic spectral features of phenylalanine (see the preceding paper), even in the presence of large absorbance bands originating from the ironsulphur centre and one tyrosine.…”
Section: Methodsmentioning
confidence: 99%
“…4) Addition of substrate then occurs to the C(5) carbonyl of PQQ (covalent catalysis) in the oxidised form of MDH, followed by electron transfer [29]. In analogy with Hyphomicrobium MDH, the enzyme from M. marina is specifically oxidised by cytochrome CL [4].…”
Section: The Catalytic Cyclementioning
confidence: 99%